DEVELOPMENT OF GIS SOFTWARE TO AUTOMATE MULTI-SCALE GRID SYSTEM AND POPULATION DISTRIBUTION FOR DETERMINING ENVIRONMENTAL SUPPORT AND CAPACITY (D3TLH) - Irwanto
The Indonesian Ministry of Environment and Forestry mandates the Central and Local Governments to determine the Environmental Carrying Capacity (ECC) in their respective regions. In fact, there is a diversity of government capacity in managing spatial data. IMSGS (Indonesian Multi-Scaled Grid System) QGIS Plugin can solve these problems by minimizing errors due to negligence, shortening processing time, and can be accessed easily without charge through the QGIS Plugin Repository. The main references in writing this plugin algorithm are PerMen LH Number 17/2009 concerning Guidelines for Determining Environmental Carrying Capacity, PyQGIS Developer Cookbook, and previous research related to the Indonesian Multi-Scaled Grid System and ECC determination. IMSGS QGIS Plugin offers automation of grid creation, population distribution, and calculation of water and food ECC status using multi-scaled grid system. IMSGS QGIS Plugin has passed the comparative testing process with the approved data and the plugin testing process by prospective users. The accuracy score of each algorithm was 100%, the efficiency score was 436.5% - 54015%, and it received very good responses in the aspect of interface convenience and ease of getting technical support from the questionnaire respondents.